2024
DOI: 10.3390/batteries10010032
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heat Transfer Enhancement Techniques on a Scalable Novel Hybrid Thermal Management Strategy for Lithium-Ion Battery Packs

Seham Shahid,
Martin Agelin-Chaab

Abstract: This paper introduces a novel hybrid thermal management strategy, which uses secondary coolants (air and fluid) to extract heat from a phase change material (paraffin), resulting in an increase in the phase change material’s heat extraction capability and the battery module’s overall thermal performance. A novel cold plate design is developed and placed between the rows and columns of the cells. The cold plate contains a single fluid body to improve the thermal performance of the battery module. Experimental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Heat pipes and fins have been found to be effective cooling devices for BTMS [9][10][11][12][13][14][15][16][17]. Other approaches include using thermoelectric cooling techniques [18][19][20][21], manifold [22][23][24][25][26], cell arrangement [27], battery pack layout within the battery cabin [28], cooling channels [29][30][31][32][33], cold plates [34,35], and nanofluids [36][37][38][39]. On the other hand, Khateeb, et al [40], Duan and Naterer [41], Li, et al [42], and Wilke, et al [43] have experimentally confirmed that PCMs offer a significant improvement to BTMS.…”
Section: Introductionmentioning
confidence: 99%
“…Heat pipes and fins have been found to be effective cooling devices for BTMS [9][10][11][12][13][14][15][16][17]. Other approaches include using thermoelectric cooling techniques [18][19][20][21], manifold [22][23][24][25][26], cell arrangement [27], battery pack layout within the battery cabin [28], cooling channels [29][30][31][32][33], cold plates [34,35], and nanofluids [36][37][38][39]. On the other hand, Khateeb, et al [40], Duan and Naterer [41], Li, et al [42], and Wilke, et al [43] have experimentally confirmed that PCMs offer a significant improvement to BTMS.…”
Section: Introductionmentioning
confidence: 99%